(untitled) (AGROINNOVATSIYА, 2024)
The normal physiological condition, sexual activity and high seed production of breeding bulls is not only provided by protein in food, but also provided by microbiological synthesis in the large stomach. Therefore, it is desirable that the ratio of sugar and protein in the diet is around 0.8-1.2, for this, 5-8 kg of beets or 3-4 kg of sugar beets are included in the diet.